Sistem Informasi Geografis Potensi Sumber Daya Kelautan Berbasis Android - Saian, Pratyaksa Ocsa Nugraha; Pratama, Raka Arya; Susetyo, Yerymia Alfa (Jurnal Transformatika, 2021)
Indonesia is the biggest maritime country that has big marine resources too. It needed a good strategy so the marine resource usage can be managed well. Now, it can be helped by using information technology. The purpose of this research is to create a Geographic Information System for knowing potential marine resources in Daerah Istimewa Yogyakarta Coast. The result of this paper is a Geographic Information System that will runs in Android devices. The test results show 82,93% of users already satisfied with this application. It indicates that this application is in a Very Good category.